(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
This article explores the concepts of syllables, stress, and intonation in spoken language. Syllables serve as the basic unit of organization in speech, while stress and intonation provide meaning and emotional context. Understanding these elements is crucial for language acquisition and proficiency